Effect of Antimicrobial Edible Coatings and Modified Atmosphere Packaging on the Microbiological Quality of Cold Stored Hake (Merluccius merluccius) Fillets - X. Carrión-Granda; I. Fernández-Pan; J. Rovira; J. I. Maté (Journal of Food Quality)
The effect of whey protein isolate (WPI) coatings incorporated with essential oils (EOs) and combined with modified atmosphere packaging (MAP) on the microbiological quality of fresh hake fillets was evaluated. Fresh hake fillets were coated with different formulations of WPI-EO coatings and packaged under air and MAP conditions (50% CO2/45% N2/5% O2). When WPI-enriched films were applied with or without the presence of MAP over hake fillets with a high initial microbial population, a limited but significant effect on the microbial growth was observed. This effect was more intense on Enterobacteriaceae and H2S-producing bacteria. When hake fillets with lower initial microbial counts were treated, a more intense antimicrobial effect was observed and a synergistic effect between WPI-EO coatings and MAP was detected. A significant extension of the lag phase and reduction, primarily, on the total viable counts and H2S-producing bacteria, was detected, doubling the shelf-life of hake fillets compared with control samples. The initial microbial load of the samples is a key factor influencing the effectiveness of the treatment. The obtained results demonstrated the effectiveness of this combined strategy as a promising alternative for enhancing the microbial quality of fish products during storage at refrigeration temperatures.